Design a New Multiport DC-DC Converter to Charge an Electric Car - Amin Abedini Rizi; Ali Rezaei; Mohammadreza Ghorbani Rizi; Mohammadmahdi Aliakbari Rizi (International Journal of Robotics and Control Systems, 2022)
Due to the lack of oil and gas, electric cars have been in high demand in recent years. There are three kinds of electric vehicles, including Hybrid Electric Vehicles (HEV), Battery Electric Vehicle (BEV), and Plug-in Hybrid Electric Vehicle (PHEV).  There is no charging portion for the batteries in the HEV where the batteries are not connected to the power grid, but BEV and PHEV can be charged by a power outlet, and the number of batteries is increased. In order to charge the battery of the Electric Vehicles (EVs), there are two ways, including the power grid and renewable energies. There are already quite a few outages in many countries, and using a power grid for charging the batteries is not suitable. Therefore, the only choice is renewable energy sources such as photovoltaic (PV), fuel-cell (FC), and so on. Furthermore, to use the DC voltage of the renewable sources, two conventional DC-DC converters are required to deliver the energy of the sources to the bank of batteries. To feed the batteries, this paper proposes a two-input one output topology that contains PV, FC, and other components. Simulation results demonstrate that the presented system is improving the system because it is able to feed the batteries with low power losses and low ripples.